The Effect Of Nurse Competence And Nurse Job Design On Customer Satisfaction And Its Implications On Customer Loyalty Survey At Gaharu Medika Primary Clinic Depok - Vivi Pancasari; Y Ony Djogo Ony; Rulia Rulia (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
This study aims to analyze the effect of nurse competence and nurse job design on customer satisfaction and the implications for customer loyalty at Primary Clinics. The research method used was a survey by collecting data through questionnaires from 154 respondents who were Primary Clinic patients. Path analysis is used to examine the effect of nurse competence and nurse job design on customer satisfaction, as well as the effect of customer satisfaction on customer loyalty. The results of the study show that the competence of nurses has a positive and significant effect on customer satisfaction at Primary Clinics. Nurse job design also has a positive and significant influence on customer satisfaction. Nurse competence and job design have a positive and significant effect simultaneously on customer satisfaction at Primary Clinic. Customer satisfaction has a positive and significant effect on customer loyalty at Primary Clinics. The implication of this finding is that Primary Clinics need to continue to strengthen nurse competencies and design adequate nurse work in order to increase customer satisfaction levels. Increased customer satisfaction can help build long-term customer loyalty, which is key to Klinik Pratama's long-term success in retaining and attracting more patients. Pratama Clinic needs to continuously monitor and improve the competence of nurses and working conditions of nurses to ensure an optimal customer experience and maintain customer loyalty on an ongoing basis.